2018
DOI: 10.1111/vcp.12673
|View full text |Cite
|
Sign up to set email alerts
|

Interbreed variation of biomarkers of lipid and glucose metabolism in dogs

Abstract: Background: Markers of lipid and glucose metabolism are used in both clinical practice and research. Detection of abnormal laboratory results often relies on speciesspecific reference intervals, but interbreed variation can also affect data interpretation. Objectives:The purpose of the present study was to compare concentrations of selected biochemical variables among different dog breeds. Methods:We analyzed a database containing information on biochemical variables from 534 dogs belonging to nine different b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…This is likely possible as intraindividual variation in contrast to inter-individual variation is small. 38 Baseline fructosamine concentrations obtained before the development and diagnosis of diabetes may be a better starting point to monitor trends, than general population-based reference ranges, but studies are lacking. Unfortunately, individual set points can change over time, and a representative individual pre-disease fructosamine test series is rarely available.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is likely possible as intraindividual variation in contrast to inter-individual variation is small. 38 Baseline fructosamine concentrations obtained before the development and diagnosis of diabetes may be a better starting point to monitor trends, than general population-based reference ranges, but studies are lacking. Unfortunately, individual set points can change over time, and a representative individual pre-disease fructosamine test series is rarely available.…”
Section: Discussionmentioning
confidence: 99%
“…Possible causes of imperfect relationship between fructosamine and mean glucose concentrations are numerous and include among others breed variations, unidentified concurrent diseases influencing protein concentrations or metabolism, metabolic situations modifying glycation, the inclusion of patients with unstable glycaemia, inaccuracy of the FreeStyle Libre system when used in hypoglycaemic or dehydrated, ketoacidotic animals and finally interindividual variation of deglycation. 4,14,17,[38][39][40][41][42][43] For human diabetics with constantly higher or lower HbA1c concentrations than expected from mean glucose measurements, several authors suggested the high-and low-glycator hypothesis. 39 This hypothesis likely also applies to canine patients, and thus different dogs may require very different fructosamine target ranges in order to achieve comparable glycaemic control.…”
Section: Discussionmentioning
confidence: 99%
“…Reference intervals have been established for some species [90,91], and also some interbreed variation of APP and other biomarkers appear in the literature [92,93]. There were 15 different breeds represented in the study and no statistical difference related to breed has been observed.…”
Section: Discussionmentioning
confidence: 99%
“…13 Additionally, there is interbreed variability in sFA. 21 Thus, apparently high sFA may occur in individuals even with well-controlled DM, when treatment regimen change is unwarranted. Therefore, to further investigate the sources of discrepancies between the CS and sFA and optimise treatment, the use of additional monitoring tools to assess glycaemic control is indicated.…”
Section: Discussionmentioning
confidence: 99%
“…Aside from the possible inherent inaccuracies of clinical assessment, other factors, such as subtle inter‐ and intra‐daily glycaemic variability, short‐lasting postprandial hyperglycaemia, and changes in daily patterns of activity, appetite and insulin absorption, might contribute to increased sFA 13 . Additionally, there is interbreed variability in sFA 21 . Thus, apparently high sFA may occur in individuals even with well‐controlled DM, when treatment regimen change is unwarranted.…”
Section: Discussionmentioning
confidence: 99%